Socio-Spiritual Concepts in Zakat Worship from an Islamic Perspective - Yusdani; Bashiru Usman Jaja; Januariansyah Arfaizar (EDUCATE : Journal of Education and Culture, 2025)
Zakat is one of the pillars of Islam that has an important role not only as an obligation of individual worship, but also as a social instrument in realizing justice and community welfare. This research aims to examine social and spiritual concepts in the implementation of zakat worship according to an Islamic perspective. The approach used is qualitative-descriptive with literature studies as the main method. The results of the study show that zakat has two main dimensions: a spiritual dimension that reflects obedience to Allah, purification of the soul, and the strengthening of faith values; and the social dimension that functions as a means of wealth distribution, poverty alleviation, and strengthening social solidarity. Thus, zakat is not only a religious ritual, but also a manifestation of human values and social justice in Islamic teachings. This study recommends optimizing the management of zakat so that the two dimensions can be realized in a balanced manner in the lives of the people.